The Images of the City. Urban Jungle-Urban Desert-Urban Meadow - Grzeszczuk-Brendel, Hanna; Marciniak, Piotr (Porównania, 2024)
The article Images of the City. Urban Jungle-Urban Desert-Urban Meadow constitutes an introduction to the journal volume of the same title. It is a discussion of the main issues raised in the volume. The metaphors of the title are discussed in relation to literature, urban planning and real-life activities. Each of them describes changes in the social functioning of the city and its inhabitants. It also defines philosophical questions about the relationship between man and nature, man and the city, the city and nature. Particularly relevant is the question about contemporary metaphors of the city and discourse about culture and nature it evokes.